Differential Outcomes and Biologic Markers of Radiation-Associated vs. Sporadic Osteosarcoma: A Single-Institution Experience - Siontis, Brittany L.; McHugh, Jonathan B.; Roberts, Emily; Zhao, Lily; Thomas, Dafydd G.; Owen, Dawn; Baker, Laurence H.; Biermann, J. Sybil; Schuetze, Scott M.; Chugh, Rashmi (Frontiers in Oncology, 2020)
Background: Radiation-associated osteosarcoma (RAO) is a rare, life-threatening complication from radiation. Many physicians presume RAO has a worse prognosis than sporadic osteosarcoma (SO), although limited objective data exist. We conducted a retrospective study comparing these entities. Methods: We identified adults treated at our institution with osteosarcoma (1990-2016) and categorized tumors as SO or RAO based on location within a prior radiation field. We extracted data on demographics, treatment and primary malignancy and examined available tumor samples for MTA-1 and ezrin using immunohistochemistry (IHC). Results: Of 159 identified patients, 28 had RAO, diagnosed at a median interval from radiation of 11.5 years (1.5-28 years). Median follow-up was 2.8 years (0.1-19.6 years). Median progression free survival (PFS) and overall survival (OS) were not significantly different in SO vs RAO patients with metastases; PFS 10.3 months vs. 4.8 months (p=0.45) and OS 15.6 months vs. 6.1 months (p=0.96), respectively. For localized disease, median relapse-free survival (RFS) and OS were significantly different, NR vs. 12.2 months (p<0.001) and NR vs. 27.6 months (p=0.001) in SO vs RAO, respectively. On IHC, there were significant differences in distribution of high, intermediate or low MTA-1 (p=0.015) and ezrin (p = 0.002) between RAO and SO tumors. Conclusions: Patients with metastases at diagnosis fared poorly irrespective of prior radiation. RAO patients with localized disease had worse outcomes without detectable differences in therapy rendered or treatment effect in resected specimens. Higher expression of MTA-1 in RAO patients may suggest an underlying difference in tumor biology to explain differences in outcomes.